Study on the Effect of Embankment Soil Layers on Stress-strain Characteristics - Salmasi, Farzin; Abraham, John (Recent Progress in Plant and Soil Research Vol. 4, 2021)
Dam embankments are complex geotechnical structures. Deformation of an earth dam is a complex process which involves nonlinear behavior of the construction materials, interactions between the structure and the underlying soil and rock strata, influence of the water load on the structure and on the foundation bedrock, and the effects of water saturation. In design of earth dams, the finite element method (FEM) is very often used to predict displacements, strains, and stresses in the structure caused by changeable loading or boundary conditions. Deformation of an embankment dam starts occurring during the construction of the dam. These deformations are caused by the increase of effective stresses during the construction of the consecutive layers of earth material and also by the effects material creep. In this study, the Alavian earth dam was selected. The settlements from single layer embankment simulations were compared with the settlements calculated for 3, 7, 10 and 15 soil layers used in the construction process. Results show that maximum displacement in a single layer dam happens in the crest of the dam. Increases in embankment layers result in the maximum displacement creation in the middle of the downstream shell. The simulation layers for the construction have little effect on the stresses in the dam; however, that may cause a significant effect on the deformations of the dam. The largest lateral displacement of 9 cm and the maximum settlement of 1.3 m are both located at the center of the dam and the lateral displacement and settlement decreases gradually from the center to both abutments. Moreover, greater settlements were observed on the downstream side. The lateral displacements are dominated by the hydraulic pressure of the water.